FinTech: a literature review of emerging financial technologies and applications - Gang Kou; Yang Lu (Financial Innovation)
Abstract Future financing has the potential to evolve into a forward-looking and ingenious system that can enrich diverse technologies. This investigation focuses on five attractive emerging technologies tied to the finance, namely artificial intelligence (AI), machine learning, blockchain, augmented reality (AR)/virtual reality (VR), and quantum mechanics. Within the financial milieu, there is an ongoing pursuit for more precise, optimized, secure, and agile solutions capable of managing multifarious financial undertakings. Emerging technologies present remarkable modalities for achieving these objectives. This scholarly exposition expounds upon the creation of emerging technologies within the financial world, while concurrently deliberating upon the prospective applications of these technologies within financial systems. Given the nascent stage of development that characterizes these emerging technologies, the advancement of financial performance emerges as a substantial challenge owing to both technological and operational advantages. Technology-oriented financing has emerged as an essential trajectory for shaping the future of finance.